2021
DOI: 10.7860/jcdr/2021/46815.14432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Truenat MTB/RIF Test in Comparison with Microscopy and Culture for Diagnosis of Extrapulmonary Tuberculosis in a Tertiary Care Centre

Abstract: Introduction: Worldwide, Extrapulmonary Tuberculosis (EPTB) accounts for 15-20% of all cases of TB. The diagnosis of EPTB is a big challenge, as the number of Mycobacterium tuberculosis(MTB) bacilli in the tissues and other organs is often very low. Truenat MTB/RIF (rifampicin) is a novel method, which is battery operated, point-of-care and chip-based Real Time Polymerase Chain Reaction (RT-PCR) micro device. Aim: To evaluate Truenat as a screening test in the diagnosis of EPTB in comparison with microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
4
5
0
Order By: Relevance
“…Jose et al . (2021) utilized Truenat to evaluate 248 EPTB specimens (including 63 urine specimens), wherein only nine EPTB specimens were found to be positive but none of urine specimens was positive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jose et al . (2021) utilized Truenat to evaluate 248 EPTB specimens (including 63 urine specimens), wherein only nine EPTB specimens were found to be positive but none of urine specimens was positive.…”
Section: Resultsmentioning
confidence: 99%
“…Letters in Applied Microbiology 75, 857--868 © 2022 The Society for Applied Microbiology.diagnosis by this assay Jose et al (2021). utilized Truenat to evaluate 248 EPTB specimens (including 63 urine specimens), wherein only nine EPTB specimens were found to be positive but none of urine specimens was positive.Contrarily, Chen et al (…”
mentioning
confidence: 99%
“…GeneXpert® Mycobacterium tuberculosis /rifampicin (MTB/RIF) or Truenat® assay was performed as per the manufacturer's instructions [ 6 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies from Chandigarh documented a sensitivity of 66.6% and 70% in Truenat testing of vitreous fluid and ileocecal biopsy specimens respectively [6] , [7] . A study from Kerala that tested different extrapulmonary specimens demonstrated 100% sensitivity of Truenat testing for M.tuberculosis diagnosis [8] . Since WHO’s endorsement of Truenat testing in 2020 [9] , the test has been deployed in all the peripheral health centers for patient management under programme which involves EPTB diagnosis as well.…”
Section: Introductionmentioning
confidence: 99%